2016
DOI: 10.1002/admi.201600517
|View full text |Cite
|
Sign up to set email alerts
|

Superamphiphobic, Magnetic, and Elastic Silicone Sponges with Excellent Temperature Stability

Abstract: separation, drug delivery, sensor and catalysis, etc. [2] With the fast development of superhydrophobic surfaces, many superhydrophobic 3D-PMs including sponges, foams and aerogels with excellent properties have been created by combining appropriate surface roughness and materials with low surface energy. [3] A variety of methods, such as 3D printing, [1c] dip-coating, [3b] template method, [4] and sol-gel method, [5] have been used to prepare superhydrophobic 3D-PMs. Lee et al. prepared superhydrophobic 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…The sponges were also superhydrophobic and superoleophilic, quickly absorbed floating oils on the water surface and also displayed high mechanical properties. Other materials were also used in the literature [29][30][31][32][33][34][35]. Inspired by marine mussel adhesive, Jiang et al used dopamine to link Fe 3 O 4 nanoparticles on electrospun PVDF [29].…”
Section: Magnetic Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…The sponges were also superhydrophobic and superoleophilic, quickly absorbed floating oils on the water surface and also displayed high mechanical properties. Other materials were also used in the literature [29][30][31][32][33][34][35]. Inspired by marine mussel adhesive, Jiang et al used dopamine to link Fe 3 O 4 nanoparticles on electrospun PVDF [29].…”
Section: Magnetic Fieldmentioning
confidence: 99%
“…Zhang et al reported superamphiphobic elastic and magnetic silicone sponges with excellent thermal stability [31]. Their sponges were prepared by hydrolytic condensation of methyltrimethoxysilane, dimethoxydimethylsilane in the presence of Fe 3 O 4 @SiO 2 nanoparticles and finally fluorinated.…”
Section: Magnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to fabricate superhydrophobic surfaces, addition of various nanoparticles such as silver, SiO2, TiO2, Fe3O4, ZrO2 in combination with low surface energy materials such as fluorinated compounds and polymers have been reported in literature [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] Moreover, if the amphiphobicity is sustained throughout the whole monolith material volume, it can foster formation of fresh re-entrant surface with amphiphobic property aer removed of the uppermost damaged layer. 22,23 In our previous work, we fabricated superhydrophobic elastic silicone rubber with excellent mechanical durability and showed the superhydrophobicity when exposed to harsh environments such as strong corrosion, extremely low temperature, various external damages, especially high mechanical stress. 24 In this work, we present a template-free procedure for the fabrication of marshmallow-like silicon monoliths with superhydrophobic and oleophobic properties.…”
Section: Introductionmentioning
confidence: 99%